Lempu Culture on Mandatory Compliance Taxes During the Covid'19 Pandemic - Daud, Dahniyar; Haliah, Haliah; Kusumawati, Andi; Rasyid, Syarifuddin (International Journal of Halal System and Sustainability https://jurnal.narotama.ac.id/https://www.spb.gba.gov.ar/campus/https://conference.trunojoyo.ac.id/https://ojs.ucp.edu.ar/https://libros.cimsur.unam.mx/https://ojs.stikesmucis.ac.id/http://medi, 2023)
Taxes are one of the largest sources of state revenue in almost all countries, but the level of tax compliance is still relatively low, including in Indonesia. Tax compliance can be defined as a condition where the Taxpayer fulfills all tax obligations and doing the taxation rights. Before the new normal during the covid'19 Pandemic, the level of compliance was studied by many researchers with various results and variables. This study tries to look at the level of tax compliance during the covid'19 pandemic by raising the lempu culture variable as local wisdom. Does the lempu culture affect taxpayer compliance during the covid'19 pandemic in the Makassar. This study explores the role of lempu culture on taxpayer compliance during the covid'19 pandemic in Makassar. This study uses quantitative data, the data that obtained in the form of numbers from the results of questionnaires and data that published by official institutions, internet and the other relevant data that needs by researcher. The population in this study were all registered taxpayers at Pratama Tax Service Office of Makassar. And the sample research used purposive sampling method with the type of sample selection based on sampling considerations. The data analysis technique used in this research is Linear Regression. The lempu culture in the Bugis Makassar society which is related to taxpayers is explained that lempu is one of the attitudes of taxpayers to comply with tax regulations without influence of other people or the tax authorities (fiscus) as a form of self-assessment system. This research was conducted during the covid'19 pandemic, its various social restrictions are imposed by the government. And from the results of collected questionnaires that has been processed are 40 respondents, it showed that the lempu culture had a positive effect on taxpayer compliance during the covid'19 pandemic. When this honesty is fulfilled by the taxpayer, in reporting the tax payable, the taxpayer will try to calculate, pay, and report the tax honestly in accordance with the actual conditions. Lempu (honesty) of taxpayers has a positive effect on the level of individual taxpayers compliance during the Covid-19 Pandemic, it means if the lempu (honesty) of taxpayers is high, the level of tax payers compliance to calculate, pay and report taxes will increase as well.